2001
DOI: 10.7771/2327-2937.1016
|View full text |Cite
|
Sign up to set email alerts
|

Playing the Edge: Motivation and Risk Taking in a High-Altitude Wilderness-like Environment

Abstract: for additional information. This is an Open Access journal. This means that it uses a funding model that does not charge readers or their institutions for access. Readers may freely read, download, copy, distribute, print, search, or link to the full texts of articles. This journal is covered under the CC BY-NC-ND license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 0 publications
7
80
1
1
Order By: Relevance
“…By comparison, inexperienced climbers were more extrinsically motivated, such as by getting away from it all, and socialising. Similarly, Ewert (1994) also established that, although exhilaration and excitement were important for all mountaineers, novices were more externally influenced by such climbing elements as skills development and image, intermediate-level mountaineers were motivated more by decision-making, whereas self-expression was an important internally-generated motivation for advanced-level climbers. However, in more recent research (Ewert et al, 2013) it is argued that internal and external motives have unclear boundaries, making it difficult to categorise experienced and less experienced adventurers in this way.…”
Section: Mountaineering Experience Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…By comparison, inexperienced climbers were more extrinsically motivated, such as by getting away from it all, and socialising. Similarly, Ewert (1994) also established that, although exhilaration and excitement were important for all mountaineers, novices were more externally influenced by such climbing elements as skills development and image, intermediate-level mountaineers were motivated more by decision-making, whereas self-expression was an important internally-generated motivation for advanced-level climbers. However, in more recent research (Ewert et al, 2013) it is argued that internal and external motives have unclear boundaries, making it difficult to categorise experienced and less experienced adventurers in this way.…”
Section: Mountaineering Experience Levelmentioning
confidence: 99%
“…As such, investigating this subject matter presents challenges. Outdoor recreational adventurers are often influenced by varied motives (Ewert, 1994;Mannell & Kleiber, 1997), yet some of the first studies predominantly focused on thrillseeking as a motive driving outdoor adventure activity participation. More recent studies, however, have examined wider motives , typically reflecting adventure's core elements.…”
Section: Motives Of Outdoor Adventure Activity Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported a range of meta-motivational states for participation including goal achievement, risk taking, social motivation and connection with the environment. Task mastery and self-efficacy have also been proposed as key factors that influence motivation in high risk sporting populations (Ewert, 1994;Llewellyn, Asghar, Sanchez & Jones, 2008;Slanger & Rudestam, 1997). Another emerging area of interest is affect self-regulation which considers high risk sports as a motivational source for individuals with emotional difficulties.…”
Section: Introductionmentioning
confidence: 99%